What role do self-regulatory mechanisms play in the risky use of digital media by adolescents? - Hrbackova, Karla; Hladík, Jakub; Petr Safrankova, Anna (Frontiers in Psychology, 2025)
As the time spent on digital media usage (DMU) has increased in recent years, there has been growing concern about problematic usage. The overuse of digital media affects up to a quarter of adolescents, although excessive DMU is not always associated with problematic use, a defining feature of which may be a loss of self-control. This study aims to clarify how self-regulatory mechanisms, such as trait self-control, sense of control, and self-regulation of digital media use, are related to risky DMU (excessive internet use and impulsive DMU) as well as time spent on DMU. We draw on a representative sample of 2,697 adolescents aged 11–15 years (mean age = 12.9) attending grade 2 primary schools. Our results show that adolescents with higher levels of self-control as well as a greater sense of control exhibit lower levels of risk-taking (excessive internet use and impulsive digital media use and screen time). Furthermore, increased levels of self-control as well as a greater sense of control predict higher levels of self-regulation in digital media contexts. The findings of this study provide insights regarding the importance of strengthening self-control, especially for at-risk users, and offer a perspective on the role of self-regulatory mechanisms in managing digital behavior. These factors can significantly contribute to better self-regulation of adolescents' digital behavior.